Morphometric analysis of collagen fibrils in skin of patients with spontaneous cervical artery dissection. Issue 9 (25th January 2008) - Völker, W; Ringelstein, E B; Dittrich, R; Maintz, D; Nassenstein, I; Heindel, W; Grewe, S; Kuhlenbäumer, G
Abstract : Background and aim: The aetiopathogenesis of spontaneous cervical artery dissection (sCAD) is largely unknown. Electron microscopic (EM) examination of skin biopsies of patients with sCAD revealed very subtle pathological changes of dermal connective tissue in about half of these patients leading to the hypothesis of an underlying connective tissue disorder. However, connective tissue abnormalities did not allow clear discrimination between patients and controls in our hands. Therefore, we sought to establish an objective basis for the assessment of connective tissue abnormalities in patients with sCAD using standardised morphometric assessment of collagen fibrils. Methods: In this study a blinded examination was performed of collagen in skin biopsies and it sought parameters which are able to discriminate between patients with sCAD and controls. Various morphometric parameters were compared between patients with sCAD (n = 20) and control subjects (n = 18). Results: Previously described "flower-like" collagen fibrils in skin biopsies were extremely rare in patients and controls and did not discriminate between the groups. However, they were abundant in the skin biopsy of a patient with Ehlers–Danlos syndrome type III (EDSIII) used as a reference. Morphometric parameters such as collagen fibril diameter, fibril density and relative fibril area did not discriminate between patients and controls on an individual basis, but the mean diameter of collagen fibrils in the skin was lower in patients with sCAD compared with controls while fibril density was higher resulting in nearly equal fibril areas per unit of area (relative fibril area) comparing both groups as well as individuals. Conclusions: Blinded pathological and morphometric analysis of collagen fibres in skin biopsies was, in our hands, unable to discriminate reliably between patients with sCAD and controls on an individual basis but did show differences in collagen fibril morphometry on a group basis. Furthermore, systematic and blinded pathological studies of skin biopsies in patients with sCAD and controls are needed.